Re-thinking governance and accountability of police and policing: David Bayley’s contributions to the debates - Stenning, Philip C. (International journal of comparative and applied criminal justice, 2021)
As a political scientist, David Bayley brought a very particular perspective to debates about police governance and accountability that have recently flared up again in the United States of America following the killing of George Floyd and the Black Lives Matter and “Defund the Police” campaigns that it energised. Throughout his 65-year career as the world’s leading international comparative policing scholar, Bayley wrote and spoke publicly about police governance and accountability in his native U.S.A. and many other countries around the world, as well as how it pertained to international post-conflict peace-keeping operations. In this article, I consider the proposals for reform of police governance and accountability that have been advanced following George Floyd’s death, in light of Bayley’s lifelong thoughts and proposals on this topic, culminating with his last book (which I was privileged to have co-authored with him), Governing the Police: Experience in Six Democracies.